KARAKTERISTIK MASYARAKAT KAMPUNG NAGA DALAM MENGHADAPI KUNJUNGAN WISATAWAN PADA KONDISI ADAPTASI KEBIASAAN BARU (AKB) DI DESA NEGLASARI KECAMATAN SALAWU KABUPATEN TASIKMALAYA - pipitpitria; Hilman, Iman; Indrianeu, Tineu (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2022)
This research is based on the main problem, namely what are the characteristics of the Kampung Naga community and the conditions of tourist visits to Kampung Naga during the Adaptasi Kebiasaan Baru (AKB) in Neglasari Village, Salawu District, Tasikmalaya Regency.  The research method used is a descriptive method with a quantitative approach. The results showed that the characteristics of the people of Kampung Naga have high and traditional social and cultural values. The educational and economic characteristics of the Kampung Naga community have a relatively low quality. The health quality of the people of Kampung Naga is quite good. The condition of Kampung Naga tourism during the Covid-19 pandemic generally experienced changes and decreased the number of tourists visiting. The Adaptasi Kebiasaan Baru (AKB) during a Covid-19 pandemic pattern requires tourists to implement health protocols, namely wearing masks, washing hands, maintaining distance, staying away from crowds and reducing mobility. Keywords: Community Characteristics, Kampung Naga, Adaptasi Kebiasaan Baru (AKB)